2007
DOI: 10.1136/jcp.2007.049544
|View full text |Cite
|
Sign up to set email alerts
|

D2-40 is a sensitive and specific marker in differentiating primary adrenal cortical tumours from both metastatic clear cell renal cell carcinoma and phaeochromocytoma

Abstract: D2-40 may be a useful marker for distinguishing primary adrenal cortical neoplasms from both metastatic CCRCC and phaeochromocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…The thin-walled vascular spaces around the cysts expressed CD34 only. The normal adrenal cortical cells were stained negative for D2-40 contrary to previous studies [14]. The discrepancy may be owing to different conditions in specimen fixation and immunohistochemical procedure.…”
Section: Diagnosis and Pathological Findingscontrasting
confidence: 56%
“…The thin-walled vascular spaces around the cysts expressed CD34 only. The normal adrenal cortical cells were stained negative for D2-40 contrary to previous studies [14]. The discrepancy may be owing to different conditions in specimen fixation and immunohistochemical procedure.…”
Section: Diagnosis and Pathological Findingscontrasting
confidence: 56%
“…In addition, one study has reported 100% specificity of the antibody D2-40 (anti-podoplanin) for adrenal cortical lesions, 3 but we were unable to achieve satisfactory staining and it was therefore excluded from further evaluation.…”
Section: Discussionmentioning
confidence: 94%
“…[22][23][24][25][26][27] Schacht et al 27 also demonstrated the expression of D2-40 in some other nonendothelial cells beyond the above-mentioned cells To date, there are controversies and uncertainties regarding the histiogenesis of dermatofibromas and dermatofibrosarcoma protuberans. [28][29][30][31] For dermatofibroma, various cells of origin, including fibroblast, histiocyte, and endothelial cell, have been hypothesized.…”
Section: Resultsmentioning
confidence: 99%